Isolation and Characterization of Stress-Tolerant Priestia Species from Cowpea Rhizosphere Under Drought and Nutrient Deficit Conditions - Abiala, Moses; Sadhukhan, Ayan; Sahoo, Lingaraj (Current microbiology, 2023)
This study aimed to isolate stress-tolerant phytobeneficial bacteria as bio-inoculants for cowpea's sustainable growth under drought and nutrient deficiency conditions. However, the application successful of phytobeneficial bacteria is subject to effective in vitro screening under different physiological conditions. We isolated several Priestia species from cowpea rhizosphere that tolerates polyethylene glycol (PEG6000)-induced drought and nutrient deficiency. Of them, C8 ( Priestia filamentosa ; basonym: Bacillus filamentosus ), followed by C29 ( Priestia aryabhattai ; basonym: Bacillus aryabhattai ), tolerated up to 20% PEG in a low-nutrient medium. In the presence of PEG, Priestia filamentosa and Bacillus aryabhattai exhibited optimal growth in different temperatures and pH but failed to survive at extreme temperatures of 45 °C and pH 11. Priestia filamentosa preferred L-proline and L-glutamate, while L-tryptophan and L-tyrosine were the least utilized. Interestingly, Priestia filamentosa and Bacillus aryabhattai used more complex nitrogen sources, peptone, and yeast extract, than inorganic nitrogen for growth. Most importantly, under drought and nutrient deficiency, Priestia filamentosa exhibited multiple plant growth-promoting traits and more amylase and protease production than C29. Our results indicate that Priestia filamentosa is a potential bacterium to enhance the growth of cowpea plants under stressful conditions.